Next step on 'Sum of Gaps'

Calculus Level 5

Define a 1 , n = k = 1 n ( 1 ) k + 1 k \displaystyle a_{1,n} = \sum_{k=1}^{n} \frac{\left(-1\right)^{k+1}}{k} and b 1 = lim n a 1 , n \displaystyle b_{1} = \lim_{n \to \infty} a_{1,n} .

It is known that b 1 = ln 2 \displaystyle b_1 = \ln{2} .

Next we define a 2 , n = k = 1 n ( a 1 , k b 1 ) \displaystyle a_{2,n} = \sum_{k=1}^{n} \left(a_{1,k} - b_1\right) and b 2 = lim n a 2 , n \displaystyle b_{2} = \lim_{n \to \infty} a_{2,n} .

The value of b 2 b_2 has been found at this problem .

Now a 3 , n = k = 1 n ( a 2 , k b 2 ) \displaystyle a_{3,n} = \sum_{k=1}^{n} \left(a_{2,k} - b_2\right) and b 3 = lim n a 3 , n \displaystyle b_{3} = \lim_{n \to \infty} a_{3,n} .

What is the value of 1 0 5 b 3 , \displaystyle\left\lfloor 10^5b_3 \right\rfloor, where \lfloor \cdot \rfloor denotes the floor function ?


The answer is 6814.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

敬全 钟
Nov 3, 2018

The sum we intend to evaluate is m = 1 ( n = 1 m ( k = 1 n ( 1 ) k + 1 k ln 2 ) b 2 ) ( ) . \sum^{\infty}_{m=1}\left(\sum^m_{n=1}\left(\sum^n_{k=1}\frac{(-1)^{k+1}}{k}-\ln 2\right)-b_2\right) - (*). From this problem , we know that ( n = 1 m ( k = 1 n ( 1 ) k + 1 k ln 2 ) ) = 0 1 x ( 1 + x ) 2 d x 0 1 x ( x ) m ( 1 + x ) 2 d x \left(\sum^m_{n=1}\left(\sum^n_{k=1}\frac{(-1)^{k+1}}{k}-\ln 2\right)\right)=\int^1_0\frac{x}{(1+x)^2}\ dx-\int^1_0\frac{x(-x)^m}{(1+x)^2}\ dx and that b 2 = 0 1 x ( 1 + x ) 2 d x . b_2=\int^1_0\frac{x}{(1+x)^2}\ dx. Thus, the sum labelled with ( ) (*) evaluates to m = 1 ( n = 1 m ( k = 1 n ( 1 ) k + 1 k ln 2 ) b 2 ) = m = 1 ( 0 1 x ( 1 + x ) 2 d x 0 1 x ( x ) m ( 1 + x ) 2 d x b 2 ) = m = 1 0 1 x ( x ) m ( 1 + x ) 2 d x = 0 1 m = 1 x ( x ) m ( 1 + x ) 2 d x (by Fubini’s Theorem) = 0 1 x ( 1 + x ) 2 m = 1 ( x ) m d x = 0 1 x ( 1 + x ) 2 ( x 1 + x ) d x = 0 1 x 2 ( 1 + x ) 3 d x = ln 2 5 8 . \begin{aligned} \sum^{\infty}_{m=1}\left(\sum^m_{n=1}\left(\sum^n_{k=1}\frac{(-1)^{k+1}}{k}-\ln 2\right)-b_2\right) &=& \sum^{\infty}_{m=1}\left(\int^1_0\frac{x}{(1+x)^2}\ dx-\int^1_0\frac{x(-x)^m}{(1+x)^2}\ dx-b_2\right)\\ &=&-\sum^{\infty}_{m=1}\int^1_0\frac{x(-x)^m}{(1+x)^2}\ dx\\ &=&-\int^1_0\sum^{\infty}_{m=1}\frac{x(-x)^m}{(1+x)^2}\ dx \quad \textrm{(by Fubini's Theorem)}\\ &=&-\int^1_0\frac{x}{(1+x)^2}\sum^{\infty}_{m=1}(-x)^m\ dx\\ &=&-\int^1_0\frac{x}{(1+x)^2}\left(\frac{-x}{1+x}\right)\ dx\\ &=&\int^1_0\frac{x^2}{(1+x)^3}\ dx\\ &=&\ln 2-\frac{5}{8}. \end{aligned} As such, b 3 = ln 2 5 8 b_3=\ln 2-\frac{5}{8} and so 1 0 5 b 3 = 6814. \lfloor 10^5b_3\rfloor=6814.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...